Seeds of distrust: Conflict in Uganda - Dominic Rohner; Mathias Thoenig; Fabrizio Zilibotti (University of Zurich, Department of Economics, 2011)
We study the effect of civil conflict on social capital, focusing on the experience of Uganda during the last decade. Using individual and county-level data, we document causal effects on trust and ethnic identity of an exogenous outburst of ethnic conflicts in 2002-04. We exploit two waves of survey data from Afrobarometer 2000 and 2008, including information on socioeconomic characteristics at the individual level, and geo-referenced measures of fighting events from ACLED. Our identification strategy exploits variations in the intensity of fighting both in the spatial and cross-ethnic dimensions. We find that more intense fighting decreases generalized trust and increases ethnic identity. The effects are quantitatively large and robust to a number of control variables, alternative measures of violence, and different statistical techniques involving ethnic and county fixed effects and instrumental variables. We also document that the post-war effects of ethnic violence depend on the ethnic fractionalization. Fighting has a negative effect on the economic situation in highly fractionalized counties, but has no effect in less fractionalized counties. Our findings are consistent with the existence of a self-reinforcing process between conflicts and ethnic cleavages.
Keywords: D74; O12; Z1; 330; Conflict; Trust; Ethnic Fighting; Uganda; Social Capital; Identity; Politische Unruhen; Ethnische Diskriminierung; Social Capital; Ethnische Gruppe; Uganda